2014
DOI: 10.1007/s10815-014-0190-7
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase in polycystic ovary syndrome patients undergoing intracytoplasmic sperm injection

Abstract: Although decreased SOD activity in FF has no effect on fertilization rate and/or embryo quality, serum SOD activity could be a clinical parameter for determining systemic oxidative stress in PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 19 publications
12
22
0
Order By: Relevance
“…Increased XO activity and decreased SOD activity in PCOS women indicate the increased production and (Seleem et al, 2014) and (Zhang et al, 2008), the decreased SOD activity in PCOS women in our study may be important in the pathogenesis of PCOS and its metabolic complications. This relationship may be supported by our results where we found that SOD activity was inversely correlated with TG/HDL-C, CRP, PCT, and FPG, and positively correlated with QUICKI levels.…”
Section: Discussionsupporting
confidence: 59%
“…Increased XO activity and decreased SOD activity in PCOS women indicate the increased production and (Seleem et al, 2014) and (Zhang et al, 2008), the decreased SOD activity in PCOS women in our study may be important in the pathogenesis of PCOS and its metabolic complications. This relationship may be supported by our results where we found that SOD activity was inversely correlated with TG/HDL-C, CRP, PCT, and FPG, and positively correlated with QUICKI levels.…”
Section: Discussionsupporting
confidence: 59%
“…SOD activity in PCOS serum has been reported with contradicting results [5, 12, 54-56]. The higher expression of SOD implies higher antioxidant activity in PCOS to combat higher intrinsic reactive oxygen species induced oxidative load [57].…”
Section: Discussionmentioning
confidence: 99%
“…They found that SOD levels were statistically significantly higher in women without PCOS [12]. Different results were obtained by Bausenwein et al in their study of 84 female patients undergoing IVF; the authors found no statistically significant differences in follicular fluid levels of SOD between the patients with PCOS and the rest of the group, while they also demonstrated a correlation between catalase levels and patient's body weight [11].…”
Section: Discussionmentioning
confidence: 82%
“…The balance in the oxidoreductive system depends on different factors including but not limited to superoxide dismutase (SOD) and catalase levels [8,9] [10,11]. Literature reports on the effects of these enzymes on reproduction are inconclusive [9,10,12]. Negative impact of the environment in which the egg cell grows as well as the defects of sperm DNA repair mechanisms affect the quality of the embryo and the time in which subsequent developmental stages are reached, which ultimately translates into achievement of pregnancy [13][14][15].…”
Section: Introductionmentioning
confidence: 99%